Metabolic and molecular changes associated with the increased skeletal muscle insulin action 24–48 h after exercise in young and old humans - Stephens, Francis B.; Tsintzas, Kostas (Portland Press, 2018)
The molecular and metabolic mechanisms underlying the increase in insulin sensitivity (i.e. increased insulin-stimulated skeletal muscle glucose uptake, phosphorylation and storage as glycogen) observed from 12 to 48 h following a single bout of exercise inhumans remain unresolved. Moreover, whether these mechanisms differ with age is unclear. It is well established that a single bout of exercise increases the translocation of the glucose transporter, GLUT4, to the plasma membrane. Previous research using unilateral limb muscle contraction models in combination with hyperinsulinaemia has demonstrated that the increase in insulin sensitivity and glycogen synthesis 24 h after exercise is also associated with an increase in hexokinase II (HKII) mRNA and protein content, suggesting an increase in the capacity of the muscle to phosphorylate glucose and divert it towards glycogen synthesis. Interestingly, this response is altered in older individuals for up to 48 h post exercise and is associated with molecular changes in skeletal muscle tissue that are indicative of reduced lipid oxidation, increased lipogenesis, increased inflammation and a relative inflexibility of changes in intramyocellular lipid (IMCL) content. Reduced insulin sensitivity (insulin resistance) is generally related to IMCL content, particularly in the subsarcolemmal (SSL) region, and both are associated with increasing age. Recent research has demonstrated that ageing per se appears to cause an exacerbated lipolytic response to exercise that may result in SSL IMCL accumulation. Further research is required to determine if increased IMCL content affects HKII expression in the days after exercise in older individuals, and the effect of this on skeletal muscle insulin action.